Novos letramentos e ensino de língua inglesa : uma pesquisa-ação em comunidades de baixa renda - Bezerra, Selma Silva (2011)
This study aims at investigating what kind of teaching-learning process Brazilian students go through when they learn English with focus on New Literacies for a semester in 2010. The students are from two poor communities in Maceió, in the state of Alagoas. The methodological approach was based on action research (ANDRÉ, 2004) and the collecting data procedures were field notes, questionnaires, interviews recorded in audio and video. The theoretical underpinnings were based on Applied Linguistics assumptions and on some concepts such as, new literacies (NEW LONDON GROUP,1996;COPE & KALANTZIS,2008), critical pedagogy (KRAMSCH, 1993) and active responsive production (ZOZZOLI, 2006). The results reveal that using the three activities developed in the classroom within the New Literacies pedagogy made the students participate consciously and sometimes critically. Each activity aimed at working with a different design (NEW LONDON GROUP, 1996). The first activity was for the students to produce a presentation in which students should first analyze the context of some images (visual design) in order to choose appropriate linguistic elements (linguistic design); the second one was meant to use relationship websites in order to write a profile, the task also demanded students to choose adequate linguistic elements (linguistic design); the third one aimed at producing a slogan (linguistic design) through analyzing video images (visual design) that dealt with social topics (violence, sexual abuse and environmental preservation) in which students had to build up their arguments and write about them. The results also reveal that the teacher-researcher has undergone a self-reflection process. She is more aware of her teacher talking time in classroom and feels more confident when she conducts activities in classroom and when she has to take instant decisions.